The Relationship between preoperative Smoking Cessation, Anxiety, and postoperative Anxiety and Pain: A Prospective Clinical Trial at a University Hospital in the East of Turkey by 120 Participants - Arzu Esen Tekeli; Hilmi Demirkiran; Cemal Kacar; Ufuk Duzenli; Nurcin Gulhas (Journal of the Pakistan Medical Association, 2022)
Objective: To reveal the relationship among smoking cessation before surgery, pre- and post-operative anxiety, and pain among chronic smokers. Method: The randomized controlled prospective clinical study was conducted in 2018 on the east of Turkey, in Van Yuzuncu Yil University Dursun Odabas Medical Center in city of Van. After approval from the ethics committee participants of either gender aged 20-60 years scheduled to undergo rhinoplasty surgery and graded as American Society of Anaesthesiologists I–II were included. The participants were categorised into smokers group S and non-smokers group NS. Spielberger State-Trait Anxiety Inventory values for preoperative period, postoperative 0, which is the moment when the modified Aldrete score is 9, as well as for 2, 4 and 6 hours, and visual analogue scale values for the postoperative 0, 2, 4 and 6 hours were recorded. Data was analysed using SPSS 26. Results: Of the 120 patients, there were 60(50%) in group S; 28(46.7%) females, 32(52.3%) males, overall mean age 33.0±9.7 years. In group NS, there were 34(56.7%) females and 26(43.3%) males with an overall mean age of 34.7±10.1 years (p 0.05). Group S had Spielberger State-Trait Anxiety Inventory preoperative and postoperative values significantly higher than group NS (p 0.05). While the values for postoperative 4 and 6 hours increased in group S, corresponding values decreased in group NS (p 0.05). Conclusion: High anxiety scores in preoperative period appeared to be associated with stress from surgery and anaesthesia and could have been caused by smoking dependency during the preoperative and postoperative periods.